Long-term forest use results in community plant functional trait convergence in a subtropical seasonally dry forest - Conti, Georgina (2016)
Fil: Conti, Georgina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Biología Vegetal; Argentina.